2021
DOI: 10.1021/acs.jpcc.0c10080
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Activation and Capture on a Si-Doped h-BN Sheet: Insight into the Local Bonding Effect of Single Si Sites

Abstract: Inert CO2 is only physically adsorbed on the surface of h-BN and graphene two-dimensional (2D) materials. However, a Si-doped h-BN sheet is able to capture CO2 directly through chemisorption under mild conditions. Herein, first-principles calculations and ab initio molecular dynamics (AIMD) simulations have been performed to explore the interaction between CO2 and the Si-doped h-BN sheet, and CO2 activation and chemisorption at the SiN3 site are predicted to be exothermic (−0.22 eV) and almost barrier free (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Considering the dual role of the Al center in (BDI)­Al­(I) ( 1 ) as both a Lewis base and a Lewis acid, we expect that this compound could aid in the capture and activation of CO 2 . Computationally, it has been shown that the Si center of SiN 4 dispersed on a two-dimensional SiN 4 C 4 monolayer or doped on an h-BN sheet, which has an electronic structure similar to that of Al­(I), can effectively capture and activate CO 2 . , Geometry optimization of (BDI)­Al­(I) with CO 2 ( 1 -CO 2 ) at the M06-2X-D3/6-311++G­(d,p) level shows that CO 2 is perpendicular to the six-membered ring with one oxygen approaching Al from the top and the carbon bonding to Al in the plane (Figure ). Remarkably, the initially linear OCO angle bends to 125.6° and the CO bond involved in the interaction with the Al center is stretched from 1.155 to 1.390 Å, close to the single C–O bond distance of 1.43 Å in esters.…”
mentioning
confidence: 99%
“…Considering the dual role of the Al center in (BDI)­Al­(I) ( 1 ) as both a Lewis base and a Lewis acid, we expect that this compound could aid in the capture and activation of CO 2 . Computationally, it has been shown that the Si center of SiN 4 dispersed on a two-dimensional SiN 4 C 4 monolayer or doped on an h-BN sheet, which has an electronic structure similar to that of Al­(I), can effectively capture and activate CO 2 . , Geometry optimization of (BDI)­Al­(I) with CO 2 ( 1 -CO 2 ) at the M06-2X-D3/6-311++G­(d,p) level shows that CO 2 is perpendicular to the six-membered ring with one oxygen approaching Al from the top and the carbon bonding to Al in the plane (Figure ). Remarkably, the initially linear OCO angle bends to 125.6° and the CO bond involved in the interaction with the Al center is stretched from 1.155 to 1.390 Å, close to the single C–O bond distance of 1.43 Å in esters.…”
mentioning
confidence: 99%
“…The growing global climate change caused by the excessive emission of carbon dioxide (CO 2 ) is triggering a tragic environmental crisis and threat to social development. Electrochemical reduction of CO 2 (CO 2 RR) to valuable chemical fuels under ambient conditions has been proved to be a particularly appealing proposal for achieving carbon-neutral energy cycle, which is powered by the electricity generated from renewable energy sources. However, there still remains a grand challenge to render the broad application of the early stage technology due to the robust chemical inertness of CO 2 with two extremely stable CO bonds and the competition of the hydrogen evolution reaction (HER) in aqueous electrolytes. Therefore, it is imperative to develop economically viable catalysts with high catalytic activity and product selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al introduced Si dopants during the CVD growth process of graphene and successfully synthesized Si-doped graphene sheets . Inspired by these remarkable advancements, we designed various 2D monolayers with the atomically dispersed Si, including a Si-doped h-BN sheet and a series of Si-coordinated N-doped graphene monolayers, and further explored their applications to activation and electrochemical reduction of CO 2 . , …”
mentioning
confidence: 99%
“…Previous studies have explored its potential for CO 2 capture and activation, although CO 2 could be only physically adsorbed on the h-BN surface . To address this limitation, we tried to introduce atomically dispersed Si sites into the h-BN sheet to promote its activity toward CO 2 activation, and thus a Si-doped h-BN sheet containing SiN 3 moiety by replacing B with Si was constructed, as shown in Figure a . The first-principles calculations revealed that the atomically dispersed Si site indeed can activate CO 2 to yield a chemisorption configuration of CO 2 with a remarkably low energy barrier of 0.03 eV.…”
mentioning
confidence: 99%
See 1 more Smart Citation